The influence of energy boost and springblade footwear on the kinetics and kinematics of running - Sinclair, J.; Dillon, S. (Human Movement, 2016)
Purpose. The aim of the current study was to comparatively examine the effects of energy return, spring and conventional footwear on the kinetics and kinematics of running.